Recovery housing and on-the-ground research priorities: a scoping study through the lens of community based participatory research - Hibbard, Patrick F.; Tice, Cameron W.; Dewey, Jodie M.; Gallardo, Kathryn R.; Tompkins, James; Bell, Justin S.; Sandhu, Jasleen; Cruz, Michelle A.; Babbitt, Kathryn; Mericle, Amy A.; Sheidow, Ashli J. (Frontiers in Public Health, 2025)
IntroductionThough communities have featured recovery housing (RH) for several decades, the base of evidence for best practices continues to grow – especially evidence needed by, and known to, those who operate and receive these services. The Initiative for Justice and Emerging Adult Populations (JEAP) engaged with three community boards (CBs) – consisting of young adults with experience in recovery from substance use issues, people who have a history of criminal legal system involvement and recovery, and payers and provider of substance use services and harm reduction – to understand on-the-ground priorities for research into recovery support services.MethodsJEAP engaged with the CBs using community-based participatory research, resulting in 12 overarching categories of research priorities, including RH. Each category contains a general problem statement, as well as testable research questions stemming from the priorities identified by the CBs. It remains to be seen, though, if research has answered them. This study used these research questions as the basis for an adapted scoping study, querying extant literature on these research priorities.ResultsThese efforts resulted Our search found 132 peer-reviewed studies of RH since 1984, 111 of these pertaining to the CB’s research questions. These, however, were heavily weighted toward those providing fewer services and supervision (80%), and the research questions focused on RH operations (57%), though more recent efforts have investigated populations served (37%).DiscussionThough many RH studies fell within JEAP research questions, the literature has yet to reach an overarching consensus on best practices within each. Given the high degree of variation between types of RH programs and between geographic locations, such consensus may not be feasible or even desirable. Key elements of effective RH operations are discussed providing useful information for both researchers and practitioners to consider, as well as recommendations for future research.